Ecological, Social, Economic Sustainability Policies and Fish Cultivation in Reservoir Waters - Fatmawati Fatmawati; Mona Gusfira; Dedi Agustanto; Eni Kamal; Isril Berd; Abdul Razak (Pascasarjana, Universitas Negeri Padang, 2023)
Dams have a very large ability to develop fish culture, then from that the development of fish culture grows rapidly. This rapid progress greatly resulted in a reduction in water quality, good for the life and progress of fish and their food-living creatures. This dam is also used for capturing fisheries, floating net cage aquaculture (KJA), transportation, and tourism. This research is literary research from several posts that study articles on the status of the sustainability of dams and the sustainability of KJA aquaculture in multidimensional sustainability (environmental, economic, and social sciences). Based on the results of policy research on the sustainability of environmental, social, and economic science and fish farming in dam waters, the sustainability of dams as well as the sustainability of KJA cultivation are very supportive of one another. Prolonged management of the dam will help the sustainability of KJA cultivation.